Comparing digital replantation versus revision amputation patient reported outcomes for traumatic digital amputations of the hand: A systematic review and meta‐analysis. Issue 5 (3rd April 2021) - Stone, Nicholas; Shah, Ajay; Chin, Brian; McKinnon, Victoria; McRae, Matthew
Abstract: Purpose: Adults with traumatic digital amputation (TDA) of the hand may be managed with replantation or revision amputation. To date, there is no systematic review evaluating patient reported outcomes (PROs) comparing replantation versus revision amputation. Methods: Three databases (MEDLINE, EMBASE, and PubMed) were systematically searched in duplicate from inception until June 13, 2019 using Covidence software. Studies comparing replantation versus revision amputation outcomes were considered for inclusion. Methodological quality was assessed using Methodologic Index for Nonrandomized Studies (MINORS) criteria. Data were pooled in a random‐effects meta‐analysis model using Revman software. Certainty of evidence was evaluated using Grading of Recommendations, Assessment, Development, and Evaluations (GRADE). Results: Of 4350 studies identified, 12 retrospective cohort studies met inclusion criteria and compared TDA outcomes for replantation ( n = 717; 82.9% male; mean age 40.3) versus revision amputation ( n = 1046; 79.8% male; mean age 41.7). The overall replantation survival rate was 85.3%. The average MINORS score was 57% (13.75/24). Replantation of the thumb had a superior Michigan Hand Questionnaire (MHQ) score (+11.88, 95% CI [7.78–15.99], I 2 = 21%) compared with revision amputation. Replantation of single non‐thumb digits had a superior MHQ score (+5.31, 95% CI [3.10–7.51], I 2 = 67%) and Disability of Arm, Shoulder, and Hand (DASH) score (−5.16, 95% CI [−8.27 to −2.06], I 2 = 0%) compared with revision amputation. Most patients in the meta‐analysis were from Asian populations (87.9%). Conclusion: There is low‐quality evidence that thumb replantation achieves superior PROs compared with revision amputation, which may be clinically important. Replantation of single non‐thumb digits also yielded superior PROs, which is likely not clinically important and based on very low‐quality evidence. Future studies with populations outside Asia are required to determine if PROs vary based on cultural differences toward digital amputation.